Letter from Jane Tolmach to Chairpeople, Politics Committee Women For: - Jane Tolmach:::::: (1976)
This three-page set of documents reflects mutual support between Jane Tolmach and the organization WOMEN FOR: in May 1976. On May 7, WOMEN FOR: confirmed its endorsement of Tolmach's Assembly candidacy and invited her to a pre-primary event; on May 11, it issued a press release publicly listing her among its endorsed Assembly candidates for the 36th District. On May 18, Tolmach wrote to thank the group for its endorsement and financial contribution, noting that the support was especially important as her campaign funded mailings and advertising before the primary. The press release also detailed WOMEN FOR:'s broader endorsements for congressional, legislative, judicial, and local races, as well as its positions on ballot measures. Together, the documents show formal endorsement, public promotion, and financial backing from a prominent Southern California women's political organization.